2014
DOI: 10.1007/s10336-014-1072-6
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale climate variability and rodent abundance modulates recruitment rates in Willow Ptarmigan (Lagopus lagopus)

Abstract: Recruitment of juveniles is important for the size of the next year's breeding population in many bird species. Climate variability and predation may affect recruitment rates, and when these factors are spatially correlated, recruitment rates in spatially separated populations of a species may be synchronized. We used production data from an extensive survey of Willow Ptarmigan from 2000 to 2011 to investigate spatial synchrony in recruitment of juveniles within and among mountain region populations. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…com). Based on these data, number of chicks per female (hereafter "production") was estimated using generalised linear models (GLMs) assuming a binomial error structure, following the procedure outlined in Kvasnes, Pedersen, Storaas, and Nilsen (2014).…”
Section: Ecosystem Datamentioning
confidence: 99%
“…com). Based on these data, number of chicks per female (hereafter "production") was estimated using generalised linear models (GLMs) assuming a binomial error structure, following the procedure outlined in Kvasnes, Pedersen, Storaas, and Nilsen (2014).…”
Section: Ecosystem Datamentioning
confidence: 99%
“…Based on this, and observed effects on ptarmigan habitat occupancy patterns, Henden et al [ 31 ] concluded that factors other than changing rodent population dynamics may be responsible for the declining trend in Scandinavian ptarmigan. Then again, Kvasnes et al [ 32 ] observed a pronounced large-scale spatiotemporal synchrony in ptarmigan recruitment that corresponded with variation in rodent abundance. However, an effect of spring/summer climate (North Atlantic Oscillation, NAO-index, in May, June and July) had a stronger effect on recruitment of ptarmigan than rodents.…”
Section: Introductionmentioning
confidence: 98%
“…However, an effect of spring/summer climate (North Atlantic Oscillation, NAO-index, in May, June and July) had a stronger effect on recruitment of ptarmigan than rodents. Based on these results, Kvasnes et al [ 32 ] concluded that the link between rodent and ptarmigan dynamics had been weakened following the collapse of rodent cycles during the 1990s, and that climate changes lead to desynchronization.…”
Section: Introductionmentioning
confidence: 99%
“…Chávez-león et al 2004;Dzialak et al 2011;Anich et al 2013) and climate change (e.g. Kvasnes et al 2014). The home range or territory of the Galliformes and the influence factors, including habitat characteristics, were also interested by many researchers at the early stage (e.g.…”
Section: Macroscopic Ecologymentioning
confidence: 99%
“…Dzialak et al 2012;Ross et al 2016), and their results showed that the habitat use patterns of some species varied at different spatial scales (Dzialak et al 2012), whereas those of some species were similar at different spatial scales (Thogmartin 1999). As regards the temporal scale, researchers conducted these studies at different time intervals, including different seasons, life history stages or years under the background of climate changes, which further influenced the perception of habitat availability and habitat selection (Jones 2001;Dzialak et al 2011;Kvasnes et al 2014).…”
Section: Macroscopic Ecologymentioning
confidence: 99%